Regionális térszerkezeti sajátosságok Kelet-Közép-Európában és országaiban - Farkas, Máté; Szabó, Pál (Közép-Európai Közlemények, 2014)
The aim of this paper is to explore and analyze the regional specialities of Central and Eastern Europe (CEE) based on the classification of regions. In first part the theoretical and methodological foundation is summarized. One important foundation is the spatial structure, which includes the differences of the concentration of population and economy, and the inequalities of economic development in our viewpoint. The groups of regions may be prepared to analyze statistics indicators (in this case the population density and GDP per capita). In second part the changing definiton and area of Central and Eastern Europe is described based on literature review. Finally – based on our own calculations using the data of Eurostat – we classify the regions of CEE. The different categories of regions are analyzed, and the following conclusions can be drawn from the present study, in CEE there are not large homogenous macroregions, and the countries are quite different from each other in point of types of regions, and the cities determinate the regional inequalities of economic development, not only population density.